ADAPTING URBAN HEAT ISLAND MITIGATION STRATEGY ON BANDUNG DOWNTOWN AREA - Petrus Natalivan Indradjati; Iztirani Nur Aisha (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2019)
Urban Heat Island (UHI) mitigation research has been carried out for a long time but it requires to be sharpened to enrich mitigation strategies. In Bandung, maximum temperature has been increasing from 330C to 350C in 30 years. Bandung is getting hotter which can exaggerate the negative impact of UHI mainly in the downtown area. Suitable UHI mitigation strategies are needed to lower urban temperature. UHI mitigation has involved the use of heat-absorbing and covering man-made materials with vegetation such as green wall and roof system. Content analysis of UHI precedents and some preliminary studies are applied to assess prerequisites of UHI mitigation. The analysis showed adaptation opportunities of UHI mitigation strategy on buildings and environmental physical components. The mitigation strategies may vary depending on the typology of buildings (roof and wall) by using reflective materials, while outside the building by increasing vegetation to maximize evaporation to lower the temperature.